Beyond Burnout: Nurses’ Perspectives on Chronic Suffering During and After the COVID-19 Pandemic - Melissa A. Powell; Tolu O. Oyesanya; Susan D. Scott; Deborah H. Allen; AnnMarie Walton (Global Qualitative Nursing Research, 2024)
Nurses around the globe have been impacted psychologically and emotionally during and after the COVID-19 pandemic. The purpose of this study was to describe nurses’ perspectives on the concepts of compassion fatigue, second victimhood, burnout, and moral injury. Eight nurses were interviewed either individually or in groups of two. Data were analyzed using conventional content analysis. The following themes were identified: waves of compassion fatigue, traumatization within second victimhood, never the same after chronic burnout, moral injury: nurses couldn’t do their best, and connections across concepts. Results showed nurses were most familiar with burnout and compassion fatigue, which remain chronic struggles. Second victimhood and moral injury were more distinct experiences related to traumatic or morally distressing events and likely contributed to experiencing burnout or compassion fatigue. Nurses’ suffering heightened during the COVID-19 pandemic and remains prominent three years later. Future research and interventions are urgently needed globally to reduce workplace stressors and promote nurse well-being.